Extensive Genomic Rearrangements along with Distinct Mobilome and TALome are Associated with Extreme Pathotypes of a Rice Pathogen. (8th February 2020) - Kaur, Amandeep; Bansal, Kanika; Patil, Prabhu B
Abstract: Xanthomonas oryzae pv. oryzae (Xoo) is a serious pathogen of rice which displays tremendous interstrain variation. The emergence of highly-virulent strains of Xoo is a major threat to rice cultivation. Evolutionary insights into genome dynamics of highly virulent strains as compared with the less-virulent ones are crucial for understanding the molecular basis of exceptional success of Xoo as a highly evolved plant pathogen. In the present study, we report complete genome sequence of Xoo strains with extreme-virulent pathotypes (XVPs) characterized based on their reaction toward ten resistance ( Xa ) genes. One strain, IXO1088, can overcome resistance mediated by all the ten resistance genes while the other strain IXO704 cannot overcome any of them. Interestingly, our investigation revealed that XVPs display dramatic variation in the genome structure with numerous rearrangements/inversions. Moreover, XVPs also possess distinct transposon content and prophage elements that may provide genomic flux required for the acquisition of novel gene cassettes and structural changes in the genome. Interestingly, analysis of transcription activator-like effector proteins, which are major virulence determinants of Xanthomonas pathogen show marked variation in the transcription activator-like effector content and DNA binding domain of tal genes. Overall, the present study indicates the possible role of mobilomes and repetitive elements in major structural and sequence alterations, which may be leading to the emergence of novel and extreme pathotypes. The knowledge and resource of XVPs will be invaluable in the further systematic understanding of evolution and management of variant pathotypes of Xoo.